REDUCTION AND OXIDATION PROCESSES OF CHROMIUM IN HUMIC ACID SUBFRACTION-SENSITIZED PHOTOCATALYST - Uripto Trisno Santoso; Herdiansyah Herdiansyah; Sri Juari Santosa; Dwi Siswanta (Universitas Gadjah Mada, 2004)
The process of reduction and oxidation of soluble chromium in humic acid subfraction-sensitized photocatalyst was studied. Humic acid was extracted from peat soil sampled in Gambut District, South Kalimantan. Humic acid (HA) was fractionated to humic acid subfraction (HAS) by centrifugation method. ZnO and TiO2 were applied as the photocatalysts produced by Merck, suspended in solution of 2 g/L. Two germicide UV lamps 30 watt (Philip®) was placed in a box at 20 cm above the samples. The results showed that HA or HAS sensitized the photoreduction of Cr(VI) by photocatalyst. The low molecular weight of HAS is more effective to act as sensitizer than the high molecular weight one. The yield of the photoreduction of Cr(VI) with photocatalysts enhanced both in the presence of Fe(II) ion and HAS. UV irradiation of the MnO4- solutions containing Cr(III) induced the photooxidation of Cr(III) to Cr(VI). The presence of Fe(III) or HAS doesn't inhibit significantly. The inhibition is enhanced by the present of both HAS and Fe(II) or HAS and Fe(III). This inhibition is enhanced more by the presence of ZnO or TiO2 photocalysts.